PENGARUH DISCHARGE PLANNING BERBASIS VIDEO DENGAN PENDEKATAN FAMILY CENTERED NURSING TERHADAP KEMAMPUAN KELUARGA MERAWAT KLIEN SKIZOFRENIA - Nunik Purwanti; Ah. Yusuf; Suprajitno Suprajitno (Universitas Nahdlatul Ulama Surabaya, 2017)
Schizophrenia is a chronic brain disorder that affects about one percent of the population which is also commonly found in Indonesia. Based on the medical records taken from Surabaya Menur Mental Hospital in July until September 2016, the number of patients diagnosed with this disease is 439 patients. The increasing case of schizophrenia is resulted from the lack of support and role of family and their ability in taking care of patients with schizophrenia. This study used quasi-experimental design (pre-post test controlgroup design), purposed to prove the effects of video-based discharge planning using family-centered nursing on the ability of family in taking care of patients with schizophrenia. This study involved the family members of schizophrenic clients as the population in which half of them were taken as the samples: 15 repondents were chosen as the control group, whereas 15 respondents were taken as the treatment group using consecutive random sampling technique. The independent